2022
DOI: 10.1007/s13202-022-01470-9
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach of reservoir characterization of Y gas field in Central Bredasdorp Basin, South Africa

Abstract: The study attempts to address the knowledge gap in the Bredasdorp Basin Offshore South Africa by using newly acquired seismic data with an enhanced resolution, integrating core and well log to provide a solution. The main objective of this study was a volumetric sandstone reservoir characterization of the 13At1 and 10At1 sandstones deposited in the upper shallow marine environment. The results reveal four facies grouped as facies 1(claystone), facies 2(intercalation of claystone and sandstone, facies 3(medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Several authors have reported that the Bredasdorp Basin was formed in the Gondwana due to the movement of the South Atlantic along the Agulhas-Falkland Fracture Zone [20,26,29]. In addition, several authors have made significant contributions [25,27,[30][31][32][33][34] to study sedimentology, sequence stratigraphy, petroleum systems, and the regional tectonic settings of the Bredasdorp Basin. However, to date, few published works have been published on the impacts of mineral composition on the variations of flow zonation in the Bredasdorp Basin, offshore of South Africa.…”
Section: Overview Of Geological Settingmentioning
confidence: 99%
“…Several authors have reported that the Bredasdorp Basin was formed in the Gondwana due to the movement of the South Atlantic along the Agulhas-Falkland Fracture Zone [20,26,29]. In addition, several authors have made significant contributions [25,27,[30][31][32][33][34] to study sedimentology, sequence stratigraphy, petroleum systems, and the regional tectonic settings of the Bredasdorp Basin. However, to date, few published works have been published on the impacts of mineral composition on the variations of flow zonation in the Bredasdorp Basin, offshore of South Africa.…”
Section: Overview Of Geological Settingmentioning
confidence: 99%
“…The published work in the Bredasdorp Basin dealing with the classification and impact of diagenesis on the reservoir properties focused on the basin's southern part [8,20]. The characterization of the younger reservoirs in the Cretaceous age, ranging from the Valangianian to Albian age in the Bredasdorp Basin, was conducted by the authors of [21].…”
Section: Introductionmentioning
confidence: 99%